The English Teaching Style in the Merdeka Curriculum Realized through Professional Development - Moza Moulidyah; Dila Charisma; Fitri Aprianti (Proceedings Series on Social Sciences & Humanities, 2024)
The purpose of this research was to investigate English teaching styles in the Merdeka Curriculum realized through professional development. The method used was a qualitative research method with a case study design. The instrument in this study is an observation of learning videos when in-service PPG students conduct PPL. The researcher found several teaching styles used by English teachers in their learning in class such as facilitator, delegator, formal, and expert teaching styles. However, whatever teaching style the teacher uses must be by the students' learning style. This research concluded that English teachers who took part in the in-service teacher professional education (PPG) program got significant improvements and teacher skills in applying teaching styles and teaching methods were more interactive and in accordance with the principles of the Merdeka Curriculum.